Exchange rate depreciations and local business cycles: The role of bank loan supply - Thorsten Beck; Peter Bednarek; Daniel Marcel te Kaat; Natalja von Westernhagen (Deutsche Bundesbank, 2021)
This paper uses matched bank-firm-level data and the 2014 depreciation of the euro to show that exchange rate depreciations lead to increased bank loan supply of large banks with significant net foreign asset exposure. This increase in lending can be explained by a shift in credit towards both export-intensive firms and small banks without foreign asset exposure that have a higher share of exporting firms in their credit portfolio. We also find that German regions where these reallocation effects are stronger experience higher output growth. In economic terms, we show that such regions grow by 1.2 percentage points more than less exposed regions, cumulatively, in the two years after the depreciation relative to the two pre-depreciation years.
Keywords: E44; E52; G21; O40; 330; Exchange Rates; Bank Lending; Interbank Markets; Real Effects; Regional Business Cycles; Germany